2017
DOI: 10.7717/peerj.3452
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination ofPicea chihuahuanaMartinez populations on the basis of climatic, edaphic, dendrometric, genetic and population traits

Abstract: BackgroundPicea chihuahuana, which is endemic to Mexico, is currently listed as “Endangered” on the Red List. Chihuahua spruce is only found in the Sierra Madre Occidental (SMO), Mexico. About 42,600 individuals are distributed in forty populations. These populations are fragmented and can be classified into three geographically distinct clusters in the SMO. The total area covered by P. chihuahuana populations is less than 300 ha. A recent study suggested assisted migration as an alternative to the ex situ con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…Our results suggest that there are significant quantitative genetic differences among the three analyzed Picea species and that these differences are correlated with two climate variables (the mean minimum temperature in the coldest month and the summer/spring precipitation balance), supporting the hypothesis of adaptation to local conditions [6]. However, a proportion of phenotypical plasticity cannot be ruled out because the provenance trial experiment was not reciprocally carried out.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our results suggest that there are significant quantitative genetic differences among the three analyzed Picea species and that these differences are correlated with two climate variables (the mean minimum temperature in the coldest month and the summer/spring precipitation balance), supporting the hypothesis of adaptation to local conditions [6]. However, a proportion of phenotypical plasticity cannot be ruled out because the provenance trial experiment was not reciprocally carried out.…”
Section: Discussionsupporting
confidence: 54%
“…P. mexicana has only three locations, above 3000 m elevation [2,3], P. martinezii is in four populations between 1800 and 2500 m [4] and P. chihuahuana has been found at 40 sites between 2311 and 2700 m [2,5]. The Mexican spruces' distributions are fragmented in isolated populations, which could lead to phenological, morphological and genetic differentiations, partially caused by local adaptation to different soil types and climatic variables [6]. Therefore, it is important to identify the main factors responsible for such adaptation, which could be helpful in assisted migration programs, as an option for ex situ conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Jaramillo-Correa et al (2006) reported that chloroplast DNA (cpDNA) diversity in Picea chihuahuana increases from southern to northern populations. The higher level of genetic diversity in northern populations can probably be explained by the smaller spatial distances among them and, thus, the potential for higher genetic exchange and lower tendency of genetic drift and inbreeding (Dominguez-Guerrero et al 2017). Populations at the southern distribution limit, which are more fragmented and isolated from each other, are therefore probably at greater risk.…”
Section: The Case Of Three Endangered Mexican Spruce Speciesmentioning
confidence: 99%
“…] tions more severely and eventually causing an extinction vortex at the population level (inbreeding causes reduced seed set and germination potential, which leads to lower seedling recruitment, which subsequently reduces the effective population size and promotes even more inbreeding, thus repeating the cycle) (Gilpin and Soulé 1986;Menges 1991aMenges , 1991bFrankham et al 2002). Moreover, the predicted decline and eventual disappearance of suitable habitat for this species due to possible climatic change imposes a further extinction risk (Ledig et al 2010;Dominguez-Guerrero et al 2017;Pinedo-Alvarez et al 2019).…”
Section: The Case Of Three Endangered Mexican Spruce Speciesmentioning
confidence: 99%
“…To study the effect of soil properties on understory species, a sample of 1000 g was collected from the centre of each of the 20 subplots at 15 cm depth (four samples by plot); a total of 11 soil samples were obtained from the canopy cover and 9 from the gaps. In total, 25 soil variables were analyzed according to the methodology described by Dominguez-Guerrero et al [48]: concentrations (ppm) of potassium (K), magnesium (Mg), sodium (Na), copper (Cu), iron (Fe), zinc (Zn), calcium (Ca), manganese (Mn) and phosphorus (P), concentration of nitrate (NO3, kg/ha), pH, cation exchange capacity (CEC, meq/100 g soil), organic matter (%) and texture (%), among others (Table S1). The organic matter (OM) content ranged from 0.66-14.2% and the percentage water saturation from 29.5 to 80%.…”
Section: Determining the Presence Of Understorey Species Soil Variables And Canopymentioning
confidence: 99%